Palembang City Government's Political Economy Policy in Developing the Culinary Industry - Annisa Berliana, Siti; Norma Juainah; Siti Anisya (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the policies of the Palembang City Government in developing the culinary industry, focusing on the role of political, economic, and local regulatory aspects. The research employs a qualitative method with a descriptive approach. Primary data were obtained through in-depth interviews with culinary traders, consumers, and officials from the Department of Industry and the Department of Cooperatives & SMEs of Palembang City. Secondary data were gathered from policy documents, academic literature, and relevant local regulations The findings indicate that government policies, such as packaging innovation, promotion through culinary festivals, and the provision of fiscal incentives, have had a positive impact on improving product competitiveness and the quality of the business environment. However, policy implementation still faces challenges in terms of equitable access to facilities and limited assistance for small-scale entrepreneurs. Therefore, more inclusive and collaborative strategies are needed to ensure the sustainable development of Palembang’s culinary industry.